SIMCQC: sistema inteligente para monitoramento e controle da qualidade de combustível - SILVA, Reinaldo de Jesus da (2008)
The National Agency, Natural Gas and Biofuels, established the Program for Monitoring the Quality of Fuel Automotive, to evaluate continuously the quality of fuels and map the problems of non-compliance to standards. The research proposes the development of a system for monitoring the quality of fuel PASSI applying the methodology and techniques from artificial intelligence, using intelligent agents, and the JADE platform and language along with JESS Data Warehouse to create a repository of data that facilitates the management and support for decision-making of the Laboratory for Analysis and Research in Analytical Chemistry of Oil of the Federal University of Maranhão.